The Influence of Fraud Triangle Activity on Financial Stability, Financial Targets, and External Pressure in Infrastructure Companies Listed on the Indonesia Stock Exchange (BEI) 2020-2022 - Sulgiah Oktami; Abdul Salam; Hasanuddin, Hasanuddin (CV. AFDIFAL MAJU BERKAH, 2024)
This research aims to determine the influence of fraud triangle activity on financial stability, financial targets and external pressure in infrastructure companies listed on the Indonesia Stock Exchange (BEI) 2020-2022. The type of data used in this research is quantitative data with secondary data sources in the form of financial reports which can be obtained on the official website of the Indonesian Stock Exchange (BEI). The data collected was processed using the multiple liner regression analysis method with the help of SPSS version 26. The results of this research show that: (1) Fraud triangle activity on pressure has a positive and significant effect on financial stability. (2) Fraud triangle activity on pressure has a positive and significant effect on the financial target. (3) Fraud triangle activity on pressure has a positive and significant effect on external pressure.